Topics for Service Management Research – A European Perspective - Benkenstein, Martin; Bruhn, Manfred; Büttgen, Marion; Hipp, Christiane; Matzner, Martin; W. Nerdinger, Friedemann (SMR - Journal of Service Management Research, 2017)
The interdisciplinary and cross-functional commitment of the Journal of Service Management Research motivated us to define interdisciplinary topics of service research that are important both in the present and in the future. Therefore, relevant publications in this research field were examined, especially Ostrom et al. (2010, 2015), which com- prehensively addressed and collated research priorities. With that in mind, issues of 48 highly ranked service-oriented management and marketing journals from 2009 to 2015 were analysed to identify research topics of the recent past. Additionally, European scientists were interviewed on their focus in the field of service research in the previous year. The results demonstrate the vast array of management-oriented service research in Europe, but also the necessity of interdisciplinary research designs in service management.
Keywords: Service Research; Service Innovation; Service Process; Service Productivity; IT and Service; Service Networks; Sharing Economy; Human Resource Management